Making effective notes - Video Education Australasia; Image Link (Australia : Video Education Australasia, 1996)
This program examines why we make notes and details a variety of note taking techniques. The concepts of'Breaking Down the Elephant' and the'Alice Process are explained
Title from title screen
Script, John Pemberton ; camera, Philip Ashton ; edit, John Pemberton, Philip Ashton
Narration: Justin Shortal
DVD format
Keywords: Note-taking; Study skills